Morning glory optic disc anomaly associated with retinal detachment in a 9-year-old northern Nigerian male child: a case report - Madaki, Saudatu U.; Borodo, Sakinatu B.; Hassan, Sadiq; Ibrahim, Suleiman A.; Ebisike, Philips I.; Habib, Saudat G.; Sani, Rabi Y. (International Journal of Research in Medical Sciences, 2024)
Morning glory syndrome (MGS) is uncommon in Nigeria as is less commonly seen in Africans. It is one of the congenital excavated optic disc dysplasia apart from optic disc coloboma and peripapillary staphyloma. We report a case of morning glory disc anomaly (MGDA) with associated retinal detachment in a 9 year old boy, who presented with complaint of poor vision in the left eye incidentally noticed when he covered the right eye following a trivial trauma to the eye. Ocular examination revealed the best corrected visual acuity of 6/5 in the right eye and no perception of light (NPL) in the left eye. Cycloplegic refraction with tropicamide and cyclopentolate was OD: -0.50DS/-0.50DC×180 in the right eye and OS: -6.00DS/-0.50DC×180 in the left eye. He was not fixating with the left eye on cover test but demonstrated a 4-degree exotropia assessed with a prism bar. Anterior segment examination revealed a normal finding except for an afferent pupillary defect in the left eye. Funduscopy was normal in the right eye, but left eye revealed a large excavated optic disc with a central area of fibroglial tissue, multiple thin blood vessels emerging from the edge of the disc running radially in an abnormally straight course over the peripapillary retina. There were areas of peripapillary pigmentary changes and retinal detachment. MGS is an anomaly of the Optic nerve head usually presented with different ocular and non-ocular abnormalities, and it may be the cause of severe visual impairment in early childhood and subsequent development of amblyopia.